A Simple Analytical Method for Determining Basic Hydrodynamic Characteristics of Hybrid Fluidized-Bed Air-Lift Apparatae - Tabiś Bolesław; Boroń Dominika (Chemical and Process Engineering)
A simple analytical method for determination of basic hydrodynamic characteristics of hybrid fluidized-bed air-lift devices was presented. These devices consist of two parts: a two-phase air-lift part and a two-phase liquid-solid fluidized-bed part. Forced circulation of fluid in the air-lift part is used for fluidization of solid particles in the fluidized-bed part. According to the opinion given in the literature, if such apparatus is used for aerobic microbiological processes, its advantage is lower shear forces acting on the biofilm immobilized on fine-grained material compared with shear forces in three-phase fluidized-bed bioreactors. Another advantage is higher biomass concentration due to its immobilization on fine particles, compared with two-phase airlift bioreactors. A method of calculating gas hold-up in the air-lift part, and gas and liquid velocities in all zones of the analyzed apparatus is presented.